3.5 kW bidirectionally pumped narrow-linewidth fiber amplifier seeded by white-noise-source phase-modulated laser. (20th July 2018) - Li, Tenglong; Zha, Congwen; Sun, Yinhong; Ma, Yi; Ke, Weiwei; Peng, Wanjing
Abstract: We demonstrate an all-fiber narrow-linewidth amplifier employing a bidirectional pump scheme and cascaded white-noise-source phase-modulated seed laser. The stimulated Raman scattering effect in the amplifier is investigated by substituting different types of seed lasers. The influence of pump distributions and seed injection power on mode instability (MI) in the amplifier is also experimentally investigated. As a result, a 3 dB linewidth of 0.175 nm and a beam quality of M 2   ≈  1.5 are obtained at the output of ~3 kW, without observation of MI and stimulated Brillouin scattering effect. With the further increase of pump power, MI occurs as the output exceeds 3.17 kW, along with beam quality degradation. Optical efficiency decreases to 71.5% at the ultimate output of 3.5 kW. Therefore MI becomes the main limitation to further power scaling.